Final Technical Report: Digital cropping calendar innovations in Ghana - Wilson, Michael; Danquah, Paul; Sackey, Tracy; Awotwi, John; Ofosu-Ampong, Kingsley; Abera, Wuletawu; Amankwaa-Yeboah, Patricia (2025)
This report presents the final technical outcomes of the CSIR-INSTI–CGIAR Fund-SP02 Sustainable Farming Project (Agreement No. C25ROM230) under the Excellence in Agronomy (EiA) initiative for 2025. It details key advancements in Ghana’s Digital Cropping Calendar, including API integration, multimedia advisory enhancements, and stakeholder capacity building. The report highlights collaborative efforts among CSIR-INSTI, the Alliance of Bioversity International and CIAT, and national partners toward improving data-driven, climate-smart agricultural practices for smallholder farmers.